Performance Evaluation of Different Frequency Bands of WiMAX and Their Selection Procedure - Alam, Md. Didarul; Chowdhury, Sabuj; Alam, Sabrina (International Journal of Advanced Science and Technology, 2014)
Worldwide Interoperability for Microwave Access (WiMAX) and other broadband wireless technologies are associated with a variety of frequency spectrums. It is essential to identify optimal frequency spectrum for implementing a technologically sturdy and strong WiMAX network. This paper compares different frequency spectrums centering various parameters like path loss, interference factors, coverage area, data rate, mobility, etc. This paper particularly focuses on comparison of frequency spectrums in terms of path loss using dissimilar propagation models. Simulations are done separately in three different environments (Urban, Suburban and Rural). The simulation results are compared and analyzed to identify an optimal frequency spectrum in the three different environments. The study shows that 2.5GHz frequency band performs better than 3.5GHz frequency band for the same radio frequency conditions and environments.